The Development of the Structural Relationship Model of Factors Affecting Success for Coastal Erosion Management at the Upper Gulf of Thailand - Kongdee, Supasit; Pochanart, Pakpong (Journal of Applied Economics and Management Strategy, 2021)
ABSTRACT The research aims to 1) study the direct and indirect effects of factors affecting the success in coastal erosion management in the upper Gulf of Thailand, and 2) develop and test the congruence of the measurement model and the structural equation model of the factors affecting the success of coastal erosion management in the upper Gulf of Thailand with empirical data. The conduction of research was divided into two stages. The first stage was qualitative research through 1) document analysis and 2) in-depth interview. The second stage was quantitative research by survey questionnaires, a total of 420 samples. Data were analyzed by descriptive and inferential statistics, including the analysis of structural equation model (SEM). The results of this study showed that 1) factors relating to policies, strategic plans, and laws have a positive direct effect on the integrated coastal zone management of coastal erosion and people’s participation, but has no statistically significant effect on success in coastal erosion management. The integrated coastal zone management of coastal erosion and people’s participation has a positive direct effect on the success of coastal erosion management. For indirect effects, the success in coastal erosion management factor is indirectly influenced by policies, strategic plans, and laws through the integrated coastal zone management of coastal erosion and people’s participation. 2) The developed model is found to be congruent with empirical data at a statistical significance level. Therefore, to successfully manage coastal erosion, those involved in coastal erosion management have to adopt sustainable development concepts, maintain the value of the functional structure of the coastal environment, develop maximal economic efficiency, and concern about social equity.